Cover Feature: Organic Electrosynthesis: Applications in Complex Molecule Synthesis (ChemElectroChem 16/2019). Issue 16 (26th July 2019) - Shatskiy, Andrey; Lundberg, Helena; Kärkäs, Markus D.
Abstract : The Cover Feature highlights the various complex organic molecules, which have become possible to access through organic electrosynthesis. Both anodic and cathodic reactions are discussed, showcasing the unique reactivity of electrochemically‐generated radical intermediates. More information can be found in the Review by A. Shatskiy et al. onpage 4067 in Issue 16, 2019 (DOI:10.1002/celc.201900435 ).